Shear-compression tests on stone masonry walls strengthened with basalt textile reinforced mortar (TRM). (17th January 2022) - Meriggi, Pietro; Caggegi, Carmelo; Gabor, Aron; de Felice, Gianmarco
Highlights: Cyclic shear-compression tests on TRM-strengthened stone masonry walls were performed. BTRM restored strength and stiffness of the damaged wall, increased ductility and avoided cracks concentration. The matrix had a non-negligible role in the in-plane behaviour of strengthened walls. Connectors avoided leaf separation. Anchors enhanced wall strength against toe-crushing. Design formulas proved safe albeit omitting weak failures and matrix contribution. Abstract: Textile Reinforced Mortar (TRM) composites are one of the most effective techniques to prevent failure and ensure seismic protection of unreinforced masonry in earthquake-prone areas. Aiming at assessing the suitability of this technology for irregular stone masonry walls, this study describes quasi-static cyclic shear-compression tests carried out on limestone masonry walls, typical of the UNESCO historical district of Lyon and of the Beaujolais region (France). Four medium-scale panels were tested: one unreinforced, one plastered, and two strengthened by a basalt textile externally bonded with a lime mortar (BTRM), either with or without transversal connectors and wall-to-foundation anchors. The mechanical characterization of the BTRM was carried out to highlight the dependence of the overall behaviour of walls on the characteristics of the reinforcement. Digital Image Correlation (DIC) was used to thoroughly capture damage development over the wall surfaces. Test outcomes demonstrate the effectiveness of BTRM in enhancing the shear strength and the displacement capacity of the wall. The results also show the key role of connectors and anchors and the non-negligible contribution of the mortar matrix, allowing to investigate the reliability of the design formulations provided by the current guidelines.